Spatial Analysis of Flood Vulnerability and Retention Ponds - Saputra, Erlianto Hona; Damiri, Nurhayati; Imanudin, Momon Sodik; Ngudiantoro, Ngudiantoro (Newinera Publisher, 2025)
Flooding is one of the causes of environmental damage worldwide. Several things that can affect flooding in urban areas, Palembang experiences periodic flooding problems, especially every rainy season. The data in this article consists of primary data obtained from location surveys in retention ponds, including: documentation, topography, depth of retention ponds and secondary data from related agencies, including: location maps, climatology, regional topography. Palembang City has varying levels of flood vulnerability: high (Jakabaring, Kertapati, Plaju, and Seberang Ulu), medium (Ilir Barat and Sukarame), and low (Alang-Alang Lebar). Lowland areas with poor drainage systems require more attention. Retention ponds play an important role in managing rainwater runoff, such as the Jakabaring Sports Hall (200,000 m²), Ogan Permai Indah (22,217 m²), and Brimob Demang Lebar Daun (30,000 m²). The city's topography, which is mostly flat and low, especially around the Musi River, further increases the risk of flooding.